Vibration transmission characteristics analysis of the parallel fluid-conveying pipes system: Numerical and experimental studies. (1st September 2022) - Guo, Xumin; Ge, Han; Xiao, Chunliang; Ma, Hui; Sun, Wei; Li, Hui
Highlights: A vibration transmission model for the parallel fluid-conveying pipes system is developed. The transmission characteristics are analyzed by numerical and experimental methods. Some typical parameters on the transmission characteristics of parallel pipes are explored. Abstract: Complex parallel fluid-conveying pipes system may suffer from external excitation interference at local locations, and this interference signal will be transmitted to the target position along different paths, which involves the transmission of vibration. However, the vibration transmission characteristics analysis of the parallel pipes system has been rarely incorporated in the open research of the fluid-conveying pipe. Therefore, based on the improved transfer matrix method (ITMM) and power flow analysis, a vibration transmission model for the parallel fluid-conveying pipes system is developed for the first time. The developed model has natural advantages of simple operation and high computational efficiency in evaluating the vibration transmission characteristics of parallel fluid-conveying pipes since the power flow signals containing velocity and force information are well-matched with the state vector of the proposed model. Based on the proposed model, numerical and experimental methods are respectively utilized to investigate the vibration transmission characteristics from four different positions to the target position of the system, and the main transfer path is identified by collecting the power flow signal during the vibration transmission process. It is shown that the numerical results are basically consistent with the experimental results. Finally, the effects of clamp damping, fluid velocity, and pressure on vibration transmission characteristics of the parallel fluid-conveying pipes system are analyzed. The developed model can be more targeted to find the path that needs to reduce vibration in the parallel fluid-conveying pipes system, which provides a premise for the subsequent implementation of vibration reduction designs.